THE IGBO CONCEPT OF CHI: THE DESTINY SPIRIT: . - Emegbara, Nkem L. (Journal of Dharma, 1998)
Secondly, it appears to be a universal concept. Most, if not every race, has a counterpart of Chi, which readily suggests itself whenever the Igbo concept of Chi is expressed. For example, it has been likened to the Egyptian Ka, which is regarded as the image or genius of a person, an ancestral aspect, which acts as a guide and protector of people during their lifetime'. It has also been likened to the Hebrew ruach which the Hebrews believed would enable the anointed servant to fulfil his destiny.